Useful activities to enhance the speaking skills through the use of smart board in 3rd basic education year at unidad educativa Jean Piaget Albohispano high school during the school year 2016-2017 - Malucin Guerrero, Melanny Elizabeth (2016)
The main purpose of this research project is to enhance speaking skills using useful activities through the use of smart board in third graders students at Unidad Educativa “Jean Piaget” (Albohispano) High School. For achieving this goal, the objectives were to determine the relationship between classroom activities and the development of speaking skill ability in the English language through the use of smart board. As a part of our research instruments, we have class observation, interview for the principal, surveys to teachers, students, and parents in order to know the difficulties that they are facing. Analyzing and comparing the information obtained with the instruments, it was many reasons that affected the development of speaking skill, most of them had difficulties to speak due to lack of useful activities. Later on, working on the results of teachers, parents and students we could maintain a good environment during English classes. We got a great experience with useful activities through smart board. Finally, after making conclusions, some recommendations have been made for the institution in order to improve speaking applying useful activities through the use of Interactive whiteboard…..